Investigating acceptance of marine tourism levies, to cover the opportunity costs of conservation for coastal communities - Booth, H; Mourato, S; Milner-Gulland, EJ (Elsevier, 2022)
Marine tourism is promoted as a substitute economic activity to unsustainable fishing, which is compatible with conservation. However, benefits of marine tourism do not typically accrue in small-scale fisheries (SSFs), which often bear the costs of conservation; they accrue to tourists and tourist-focussed businesses. We explored how marine tourism levies could operationalise the beneficiary-pays principle and address these cost-benefit inequities using an online contingent valuation (CV) survey to measure international tourists' willingness-to-pay (WTP) towards community-based shark conservation (N = 1033). Levies were widely supported (96%), with median and Turnbull mean WTP of US$ 10–14.99 and $22.02 per person per day, respectively. We combined these results with data from two marine tourism hotspots in Indonesia – Lombok and Pulau Weh – to explore the feasibility of implementing tourism levies to incentivize pro-conservation behaviour in local SSFs. Our conservative estimates indicate that marine tourism levies in Lombok and Pulau Weh could respectively generate US$ 2.3–10 million and US$ 300,000–1.3 million annually – several times greater than the estimated costs of conservation incentives in local SSFs. The marine tourism industry offers an under-utilised revenue stream for marine conservation, which could support policy aspirations such as ‘a sustainable and equitable blue economy’.